Brainypack: a guide to ethical savvy practices / Nor Zaini Zainal Abidin ... [et al.] - Zainal Abidin, Nor Zaini; Salamat, AzniSyafena Andin; Shawalludin, Syahrini; Aminuddin, Adnan; Azmi, Muhammad Syahmizan (2020)
Ethics is concentrated on the ability to determine what is "right?" and "wrong?" In light of this statement, civil servants are accountable for their actions and as the provider of public services; they must carry out the services in an effective and ethical manner. Under the New Public Management (NPM) reform, efforts to address ethical issues have been done by the Malaysian government with the applications of benchmarking, Total Quality Management (TQM), Key Performance Index (KPI) and as such, however it is still not fulfilled the public expectation where public complaints and mismanagement are still happened. Hence, this innovation is put forward to develop a clear principle on the ethical values among the students as the future civil servants. Ethical element covers five dimensions of integrity, responsiveness, benevolence, transparency and honesty. Specifically, the focal point of BrainyPack is to propagate understanding and enhance ethical savvy practices. It is interesting to note that, the commercialization potential towards this BrainyPack may provide platform for the students as the future civil servants to have clear knowledge, skills and abilities in determining ethical principles that need to be carried out.